The association between myopia and mental health among Chinese children in primary and secondary school: a cross-sectional study - Shijie Yu; Hongpo Yin; Wei Sun; Ruosong Yang; Ronghua Lai; Yushan Yu; Hongsheng Bi; Hongsheng Bi; Jianfeng Wu; Jianfeng Wu; Jianfeng Wu (Frontiers in Public Health)
ObjectiveThis study aimed to investigate the association between myopia and mental health among Chinese children in primary and secondary school.MethodsThis study employed a cross-sectional study design, including 1,640 children and their parents, via an online survey. The children underwent routine eye examinations including cycloplegic autorefraction. Multivariable linear and logistic regression models were used to examine the association between myopia and mental health. Multivariable linear regression analyses were performed in distinct subgroups.ResultsAmong all children, 836 children (50.98%) were boys; the mean age was 9.39 ± 2.22 years old. A decline in visual acuity last year was associated with a higher strengths and difficulties questionnaire (SDQ) total difficulties score (β = 0.564, 95% CI: 0.064, 1.064) and an increased risk of borderline mental health problems (OR = 1.863, 95% CI: 1.135, 3.057). Abnormal mental health problems were more likely to occur in myopic children than emmetropic children (OR = 3.601, 95% CI: 1.070, 12.456). The risk of abnormal mental health problems decreased with an increase in number of correctly identified the early treatment diabetic retinopathy study (ETDRS) markers (OR = 0.964, 95% CI: 0.933, 0.997). In grades 3-4, myopic children had a higher SDQ total difficulties score compared with emmetropic children (β = 1.065, 95% CI: 0.200, 1.929), and children with a decline in visual acuity last year had a higher SDQ total difficulties score than those without decline (β = 0.981, 95% CI: 0.011, 1.951).ConclusionMyopic children, especially in grades 3-4, were more susceptible to mental health problems than emmetropic peers. This shows the importance of early targeted counseling for mental health in myopic children.